STRATEGI KOMUNIKASI KEMENTERIAN ENERGI DAN SUMBER DAYA MINERAL DALAM MENINGKATKAN KINERJA WIDYAISWARA - Helmi, Ahmad; Ramadani, Thoriq (JURNAL APARATUR, 2021)
ABSTRACTA policy requires a communication strategy in its dissemination, to get support in its implementation. The State Civil Apparatus is required to provide the best performance, both in terms of individuals and organizations as the implementation of assigned tasks. This study aims to determine the communication strategy of the Ministry of Energy and Mineral Resources in improving to performance of Widyaiswara. The method used is a qualitative approach with a case study at the Apparatus Human Resource Development Center of the Agency for the Development of Human Resources, Energy and Mineral Resources, Ministry of Energy and Mineral Resources. Primary data collection through interviews with key informants and secondary data through literature review. The results of the study revealed that the communication strategy used was not optimal. This can be seen from the lack of common knowledge of communication strategies by Widyaiswara. The current communication strategy is that the communicator is the Head of the Apparatus Human Resource Development Center, the Widyaiswara Coordinator, and the Widyaiswara. The target is Widyaiswara because to improve performance it involves Widyaiswara himself. The message made is that Widyaiswara's performance can be supported by increasing Widyaiswara's competence, information systems, and collaboration. The media used are through competency development, information systems, social media, and websites. The expected impact is to increase the competence of Widyaiswara so that the quality of education, teaching, and training will be even better in the future. ABSTRAKSebuah kebijakan memerlukan strategi komunikasi dalam penyebarluasannya, untuk mendapatkan dukungan dalam implementasinya. Apratur Sipil Negara dituntut untuk memberikan kinerja terbaiknya baik dari sisi individu maupun organisasi sebagai pelaksanaan tugas yang sudah ditetapkan. Penelitian bertujuan untuk mengetahui strategi komunikasi Kementerian Energi dan Sumber Daya Mineral dalam meningkatkan kinerja Widyaiswara. Metode yang digunakan pendekatan kualitatif dengan studi kasus pada Pusat Pengembangan Sumber Daya Manusia Aparatur Badan Pengembangan Sumber Daya Manusia Energi dan Sumber Daya Mineral Kementerian Energi dan Sumber Daya Mineral. Pengumpulan data primer melalui wawancara kepada key informants dan data sekunder melalui peninjauan literatur. Hasil penelitian mengungkapkan strategi komunikasi yang dilakukan belum dilakukan secara optimal. Hal ini dilihat dari belum adanya kesamaan pengetahuan atas strategi komunikasi oleh para Widyaiswara. Strategi komunikasi yang sudah ada saat ini yaitu, komunikator adalah Kepala Pusat Pengembangan Sumber Daya Manusia Aparatur, Koordinator Widyaiswara, dan Widyaiswara. Target sasaran adalah Widyaiswara karena untuk peningkatan kinerja melibatkan Widyaiswara itu sendiri. Pesan yang dibuat adalah kinerja Widyaiswara dapat ditunjang dengan peningkatan kompetensi Widyaiswara, sistem informasi, dan kolaborasi. Media yang digunakan adalah melalui pengembangan kompetensi, sistem informasi, media sosial, dan website. Dampak yang diharapkan adalah peningkatan kompetensi Widyaiswara agar menghasilkan kualitas pendidikan, pengajaran, dan pelatihan semakin baik lagi ke depannya.